1970
DOI: 10.1126/science.167.3915.209-a
|View full text |Cite
|
Sign up to set email alerts
|

Sea Urchin Population Explosion in Southern California Coastal Waters

Abstract: Biscay which allows a 120 anticlockwise rotation of the Iberian peninsula between Eocene and Middle to Upper Miocene times. They refer several times to the fact that this va'ue is appreciably less than a rotation of 220, which they believe resulted from our paleomagnetic study of the Lisbon Volcanics (2).We must point out that in our paper (2) a post-Eocene rotation of 220 was not our unequivocal interpretation of the paleomagnetic data (3). As emphasized several times (2, 3), both graphically and otherwise, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
1
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 6 publications
0
35
1
1
Order By: Relevance
“…Population outbreaks of sea urchins have repeatedly led to destructive grazing of kelp beds in temperate coastal regions (North & Pearse 1970, Breen & Mann 1976b, Hagen 1983, Johnson et al 2005, with dramatic implications for ecosystem productivity and services (Mann 1982). Kelps create 3-dimensional structure and provide food and habitat for a diverse fauna, including many ecologically or economically valuable species, such as fish, lobsters, and sea otters (Dayton 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Population outbreaks of sea urchins have repeatedly led to destructive grazing of kelp beds in temperate coastal regions (North & Pearse 1970, Breen & Mann 1976b, Hagen 1983, Johnson et al 2005, with dramatic implications for ecosystem productivity and services (Mann 1982). Kelps create 3-dimensional structure and provide food and habitat for a diverse fauna, including many ecologically or economically valuable species, such as fish, lobsters, and sea otters (Dayton 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Grazing, especially by sea urchins, has been indicated to clear whole areas of kelp and subsequently prevent reforestation of barren areas (Aleem, 1956(Aleem, , 1973North, 1959North, , 1961McLean, 1962;Leighton et al, 1965;Neushul, 1965;Chapman, 1981). Biological or physical parameters affecting sea-urchin grazing activities therefore often result in sharp changes in kelp densities and sizes (North and Pearse, 1970;Lowry and Pearse, 1973;Estes and Palmisano, 1974;Breen and Mann, 1976;Mattison et al, 1977;Pearse and Hines, 1979;Duggins, 1980Duggins, , 1981Bernstein et al 1981). In southern California, however, Rosenthal et al (1974) found that storms and strong surge could produce kelp detachment, entanglement of drifting plants, and eventually clear whole areas which later showed increased juvenile settlement.…”
Section: Introductionmentioning
confidence: 99%
“…In addition loss of large predators and omnivores has resulted in declines in important trophic interactions within many kelp forest ecosystems (Dayton et al 1998). When left unconstrained, actively grazing sea urchins can convert multi-layered kelp forests into areas of coralline algal pavement (e.g., North and Pearse 1970, Simenstad et al 1978, Filbee-Dexter and Scheibling 2014 leading some ecologists to characterize sea urchin-kelp forest interactions as resulting in alternate stable states, regime shifts (Folke et al 2004, Petraitis and Dudgeon 2004, Estes et al 2011, or milestones of a declining ecosystem (Dayton et al 1998, Steneck et al 2004. Here the alternate regimes may persist for decades (Simenstad et al 1978, Scheibling et al 1999, Steneck et al 2002 and transitions among them have been triggered by sea urchin disease outbreaks Hines 1987, Scheibling et al 1999), physical disturbance from storms (Harris et al 1984, Ebeling et al 1985 and predation on sea urchins by sea otters, lobsters, crabs and large-bodied fishes (Estes et al 2004, Steneck et al 2004, Babcock et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…The two species are negatively associated at the scale of 25 m 2 in the shallow subtidal where their depth distributions overlap (Andrew and MacDiarmid 1999). The observed negative spatial associations among adults led early investigators to suggest that abalone and sea urchins competed for resources (North and Pearse 1970, Shepherd 1973a, Tegner and Levin 1982, Andrew and Underwood 1992. For example, Lowry and Pearse (1973) observed that when food was abundant, adult abalone displace sea urchins in crevices, demonstrating competition for space.…”
Section: Introductionmentioning
confidence: 99%